Criteria for preservation and value enhancement of Spanish-American colonial urbanism. A case study - Quevedo Rojas, Carlos (2016)
The relationship between Spain and America in the urban-planning discipline, inasmuch as it supports an ongoing cultural dialog throughout the centuries, leaves a stamp, marked as heritage, that still resists as an overseas legacy. The urban-planning experiences carried out in what Hardoy called a “classic model of Spanish-American city”, the continuous cultural exchange and the link between the ordinances and charters that marked their guidelines are clear exponents of the strong influence America had on peninsular cities, and vice versa. It was a continuous dialog carried out from both sides of the Atlantic Ocean. This ‘urban identity’, which also includes what is intangible, persists up to date as a common element that forms the base on which the fragment of a complex mosaic are molded (dependent societies, cultural juxtapositions, etc.). The preservation of these urban structures as signs of a cultural identity, after the recognition of the existing heritage elements, is a premise for the establishment of criteria for their value enhancement.